Wpływ cyrkulacji atmosferycznej na występowanie ekstremalnych opadów w Poznaniu w latach 1920-2010 - Bernas, Marcin; Kolendowicz, Leszek (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The aim of this work is to define the influence of atmospheric circulation on the occurrence of extreme precipitation in Poznań in the years 1920–2010. The daily totals for atmospheric precipitation taken at the IMGW Poznań Ławica meteorological station were used. The research also uses data collected from the NCEP/NCAR Reanalysis (Kalnay et al. 1996) concerning the distribution of atmospheric pressure at sea level, the geopotential height of 500 hPa as well as an indicator for the availability of precipitable water (PW). Data on the frequency of occurrence of Grosswetterlagen atmospheric circulation from 1920–2000 was also used.
Keywords: daily extreme precipitation; atmospheric circulation; Poznań (Poland)